Augustine and history - Daly, Christopher T.; Doody, John; Paffenroth, Kim (Augustine in conversation, 2008)
Augustine's theory and practice of historiography -- On the use and disadvantage of history for the afterlife / Peter Busch -- History as witness : Augustine's interpretation of the history of Israel in Contra faustum and De trinitate / Kari Kloos -- Augustine and the rhetoric of Roman decline / Andrew R. Murphy -- Augustine's place in history -- He promised much and did it all : Augustine and historians / James T. Carroll -- Dissent and the death penalty : developing a comparative perspective / Joseph Prud'homme -- The wage of sin is orthodoxy : the Confessions of Saint Augustine in Bayle's Dictionnaire / Ruth Whelan -- Comparisons of Augustine and later historians -- Augustine and Hegel on the history of Rome / Floy Doull and David Peddle -- A true history of ourselves : Augustine, Carlyle, and the case for biography / Marylu Hill -- Augustine and Ricoeur on the circle of time and narrative / Gregory Hoskins -- Book 18 of The city of God, Bianchini's Universal history, and the New science of Vico / Harold Stone -- Propaganda and the pornography of cataclysm : Augustine and Luigi Guicciardini's The sack of Rome / Paul R. Wright